Forecasting the development of pathogens and pests based on climate changes - Хрик, В. М.; Ситник, О. С.; Кімейчук, І. В.; Лозінська, Т. П.; Масальський, В. П. (Forestry and Forest Melioration, 2024)
Introduction Climate change in recent decades has led to a significant reduction in forest areas and has triggered various interrelated environmental challenges. One of the most serious consequences is the increasing spread of pathogenic organisms, affecting individual trees and disrupting entire forest ecosystems. Rising global temperatures and decreasing air humidity are key drivers of changes in the geographical distribution of pathogens and their vectors, exacerbating the risk of biological invasions. This study examines the main trends in the spread of pathogenic organisms to new geographic areas and identifies patterns that enable predictions regarding changes in pathogen species and their carriers. Materials and methods The research used existing data on rising global temperatures, decreasing air humidity, and their impact on forest ecosystems. Key methods included analysing the geographical distribution of pathogenic organisms, identifying patterns of their spread, and predicting changes in pathogen compositions. Additionally, an in-depth analysis was conducted on the types of pathogenic composition of microorganisms and their hosts under changing climatic conditions in Europe and Ukraine. Preventive measures aimed at mitigating the spread of forest diseases and infections were also evaluated. Results The increasing global temperatures and declining air humidity significantly alter the geographic distribution of pathogenic organisms and their vectors. A notable rise in fungal diseases, along with complex bacterial and viral infections, has been observed in many regions. These changes are closely linked to shifts in temperature regimes, which create favourable conditions for pathogens. The analysis showed that fungal diseases of trees remain dominant, while the incidence of complex bacterial and viral infections is also rising. Climate change facilitates the establishment and persistence of these pathogens in forest areas. Conclusions Increasing global temperatures and decreasing air humidity are key factors contributing to the spread of pathogenic organisms and their vectors. A change in the geographic distribution of pathogens and their carriers is the cause of invasions that negatively affect forest ecosystems. Understanding the dynamics of forest health across different regions is essential for developing targeted management strategies to mitigate the spread of forest infections. The international scientific community is actively addressing these challenges through collaborative programs that aim to coordinate global and regional efforts. Such initiatives focus on disease monitoring, preventive measures, and implementation of integrated strategies to safeguard forest biodiversity and ecological balance. 48 Refs.